The development of substance use in adolescence: results from comparing two longitudinal studies in England and Germany - Mariotti Luca; Sutherland Alex (Rivista di Criminologia, Vittimologia e Sicurezza, 2011)
This paper compares the development of alcohol and cannabis use in two English and German adolescent cohorts, using longitudinal data from ongoing studies located in Peterborough and Duisburg respectively. We set out the two studies and detail the steps taken to make the comparisons presented. Unusually, this paper assesses this development simultaneously in both cohorts, using an under-utilized variation of a well-known technique (multiple-group multiple-cohort latent growth curve modelling). In keeping with expectations from other research, there are large differences in the proportions of young people in the two countries using cannabis and alcohol. The Peterborough cohort embarked on earlier initiation of both alcohol and cannabis use, and increase their frequency of use very quickly. Despite a one year chronological gap between the two study cohorts, the 13 year old Peterborough group drink (until drunk) and smoke cannabis at the same level as the 15 year old versions of their German counterparts. Although there are some methodological differences between the two projects, the results appear to be valid.In questo articolo viene svolta una comparazione sullo sviluppo, nel corso dell’adolescenza, del consumo di droghe leggere e alcol tra un campione di giovani tedeschi e inglesi, utilizzando i dati di due studi longitudinali panel condotti rispettivamente in Germania e in Inghilterra. Per questo confronto viene utilizzata una tecnica particolare (multiple-group multiple-cohort latent growth curve modelling) che permette di osservare similitudini e differenze nello sviluppo individuale del consumo di queste sostanze nel corso del tempo, con un’attenzione particolare alle differenze tra le due coorti. Nonostante alcune differenze di tipo metodologico tra i due studi, e comunque in sintonia con studi precedenti, si notano importanti differenze tra i due campioni. Il campione inglese infatti mostra un livello di consumo più alto rispetto a quello tedesco, differenza che rimane costante nel corso di tutta l’adolescenza e per entrambi le sostanze (cannabis e alcol). Dans cet article les auteurs procèdent à une analyse comparative du développement de la consommation de drogues légères et d’alcool entre un échantillon d’adolescents allemands et anglais, utilisant les données de deux études longitudinales panel menées respectivement en Allemagne et en Angleterre. Afin d’établir cette comparaison, ils utilisent une tecnique particulière (multiple-group multiple-cohort latent growth curve modelling) qui permet d’observer d’éventuelles similitudes et différences dans l’évolution du développement de la consommation individuelle de ces substances, en focalisant l’attention sur les diversités entre les deux cohortes. Malgré quelques différences méthodologiques entre les études, les auteurs remarquent des différences importantes entre les deux échantillons. En effet, dans le groupe d’adolescents anglais, le niveau de consommation est plus élevé que dans le groupe des allemands. De plus, cette diversité reste constante durant toute la période de l’adolescence et pour les deux substances (cannabis et alcool).